N2O5 uptake coefficients and nocturnal NO2 removal rates determined from ambient wintertime measurements. Issue 16 (20th August 2013) - Wagner, N. L.; Riedel, T. P.; Young, C. J.; Bahreini, R.; Brock, C. A.; Dubé, W. P.; Kim, S.; Middlebrook, A. M.; Öztürk, F.; Roberts, J. M.; Russo, R.; Sive, B.; et al.
Abstract : [1] Heterogeneous N2 O5 uptake onto aerosol is the primary nocturnal path for removal of NOx (= NO + NO2 ) from the atmosphere and can also result in halogen activation through production of ClNO2 . The N2 O5 uptake coefficient has been the subject of numerous laboratory studies; however, only a few studies have determined the uptake coefficient from ambient measurements, and none has been focused on winter conditions, when the portion of NOx removed by N2 O5 uptake is the largest. In this work, N2 O5 uptake coefficients are determined from ambient wintertime measurements of N2 O5 and related species at the Boulder Atmospheric Observatory in Weld County, CO, a location that is highly impacted by urban pollution from Denver, as well as emissions from agricultural activities and oil and gas extraction. A box model is used to analyze the nocturnal nitrate radical chemistry and predict the N2 O5 concentration. The uptake coefficient in the model is iterated until the predicted N2 O5 concentration matches the measured concentration. The results suggest that during winter, the most important influence that might suppress N2 O5 uptake is aerosol nitrate but that this effect does not suppress uptake coefficients enough to limit the rate of NOx loss through N2 O5 hydrolysis. N2 O5 hydrolysis was found to dominate the nocturnal chemistry during this study consuming ~80% of nocturnal gas phase nitrate radical production. Typically, less than 15% of the total nitrate radical production remained in the form of nocturnal species at sunrise when they are photolyzed and reform NO2 . Key Points: The N2 O5 uptake coefficient is suppressed in ambient aerosol by nitrate. Uptake coefficients are not suppressed enough to limit the rate of NOx loss. The N2 O5 hydrolysis consumes 80% of the nitrate radical production (O3 + NO2 ).